Investigating the Efficacy of Task-Based Instruction in English Classrooms for Tenth Grade Students at Madrasah Aliyah Hubbulwathan Duri - Ika Purnama Sari; Joni Kurniawan; Dini Deswarni; Setiawati Setiawati; Iin Parlina; Khin Wint War Htun (Global READ Center, 2024)
Educational reform is a response to developments in global demands as an effort to adapt the education system to be able to develop human resources to meet the demands of the developing era. In order to be in accordance with its function and nature, ideally education should not be carried out haphazardly, but should be carried out wisely. Education includes activities carried out starting from planning, implementing activities, to evaluation and follow-up programs. The population in this study were all class X students at MA Hubbulwathan, Duri in the 2023/2024 academic year, consisting of 1 class. In this research the sample was selected using quasi-experimental research techniques (pseudo-experiments). After determining the sampling technique, in this study class X students were selected as samples from a population of one class. The results of the analysis show that assignment-based class improvement in the class is better in English subjects. Calculating the relative increase in class reached the conclusion that the proportionate rise in class was higher, namely 41.9% than on normal days. From the level of completeness of class learning that is based on assignments in class, it is better than that, where after conducting research, the results obtained were that in the experimental class of 26 students, 20 of them completed in learning effectively.